Microstructure characterization and properties of CuFeCo heterostructure alloys - Li Zhang; Jinyi Liu; Lizhen Zhan; Jie Pan; Zixie Wang; Jun Li; Xueshan Xiao (Journal of Materials Research and Technology)
The microstructure and properties of Cu66.6(FeCo)33.4 and Cu60(FeCo)40 alloys were investigated. Microstructural observations show that CuFeCo alloys have formed dual-phase heterostructures comprising face-centered cubic (FCC) and body-centered cubic (BCC) phases. The average grain size of the CuFeCo alloys after cold rolling and aging is less than 10 μm. Cu66.6(FeCo)33.4 has better elongation and electrical conductivity, while Cu60(FeCo)40 has better tensile strength, hardness, saturation magnetization, and electromagnetic interference shielding effectiveness. An increased FeCo content in a finer second phase with a larger volume fraction, leading to more phase boundaries. This enhances the strength of the CuFeCo alloys while simultaneously reducing their elongation. The obtained results can be used for further development of alloys with FCC/BCC dual-phase heterostructures.